Accumulation of long-chain fatty acids from Nannochloropsis salina enhanced by breaking microalgae cell wall under alkaline digestion. (April 2020) - Qiu, Yaojing; Frear, Craig; Chen, Shulin; Ndegwa, Pius; Harrison, Joe; Yao, Yiqing; Ma, Jingwei
Abstract: Breaking cell wall is a key step for extracting intracellular components such as proteins and lipids from microalgae. This study investigated an alternative way to disrupt microalgae cell structure by controlling pH during anaerobic digestion. The undigested lipid fractions from microalgae was preserved as long chain fatty acids (LCFAs) through pH control at alkaline condition. The optimum anaerobic hydrolysis was observed under alkaline condition at pHs 10 and 11; a maximum concentration of LCFAs (1150 mg/L) was observed at pH 11.0 on the fourth day of anaerobic digestion, which mainly consisted of palmitic acid and palmitoleic acid. Under alkaline condition, no methane was produced because of the inhibition of methanogenesis. However, the efficiency of organics hydrolysis was significantly enhanced as more soluble chemical oxygen demand (SCOD) was detected at pH 10 (11, 170 mg/L SCOD) and pH 11 (12, 273 mg/L SCOD), which was nearly twice higher than neutral pH. Also, confocal and transmission electron microscopy images illustrated the damage of microalgae cell wall and distribution of released LCFAs. The results provide insight for developing low-cost options for harvesting lipids from algal biomass. Highlights: The effects of pH on hydrolase activity during anaerobic digestion was studied. The highest concentration and yield of LCFAs were at pH 11. The highest concentration and yield of VFAs and biogas were at pH 7. The degradation of microalgae cell wall was verified at TEM.